Membangun Tingkat Kesadaran Masyarakat Dusun Paten Gunung dalam Penanganan Hipertensi - Hidayah, Nurul; Ahmad Sigit Prabowo Susanto,; Stefani Danik Kurniyati,; Ani Yuliati,; Putri Ayu Julianingsih, (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2021)
The purpose of this activity was to build the level of awareness of the people of Paten Gunung in handling hypertension. The method of implementing activities was by socializing the impact of hypertension, training in hypertension gymnastics, training in making herbal concoctions, mentoring, and evaluating. The activities were carried out on October 26, 2020; November 14, 2020; and November 28, 2020 in Paten Gunung, Rejowinangun Selatan, Magelang Selatan, Magelang with 20 elderly hypertension participants. The result was that people with hypertension are able to understand the importance of managing hypertension. The conclusion is that the people of Paten Gunung have increased their awareness in handling hypertension.